A bibliometric analysis of sepsis-induced myocardial dysfunction from 2002 to 2022 - Yao, Hanyi; Liu, Shufang; Zhang, Zhiyu; Xiao, Zixi; Li, Dongping; Yi, Zhangqing; Huang, Yuyang; Zhou, Haojie; Yang, Yifeng; Zhang, Weizhi (Frontiers in Cardiovascular Medicine, 2023)
Background: Sepsis-induced myocardial dysfunction (SIMD) has a significant contribution to sepsis-caused death in critically ill patients. In recent years, the number of published articles related to SIMD has increased rapidly. However, there was no literature that systematically analyzed and evaluated these documents. Thus, we aimed to lay a foundation for researchers to quickly understand the research hotspots, evolution processes and development trends in the SIMD field via a bibliometric analysis. Methods: Articles related to SIMD were retrieved and extracted from the Web of Science Core Collection on July 19th, 2022. CiteSpace (version 6.1.R2) and VOSviewer (version 1.6.18) were used for performing visual analysis. Results: A total of 1,076 articles were included. The number of SIMD-related articles published each year has increased significantly. These publications mainly came from 56 countries, led by China and the USA, and 461 institutions, but without stable and close cooperation. As authors, Li Chuanfu published the most articles, while Rudiger Alain had the most co-citations. Shock was the journal with the most studies, and Critical Care Medicine was the most commonly cited journal. All keywords were grouped into six clusters, some of which represented the current and developing research directions of SIMD as the molecular mechanisms. Conclusion: Research on SIMD is flourishing. It is necessary to strengthen cooperation and exchanges between countries and institutions. The molecular mechanisms of SIMD, especially oxidative stress and regulated cell death, will be critical subjects in the future.